Selection of Elite Genotypes of Coffee arabica L. to Produce Specialty Coffees - Malta, Marcelo Ribeiro; Oliveira, Antonio Carlos Baiao; Liska, Gilberto Rodrigues; Carvalho, Gladyston Rodrigues; Pereira, Antonio Alves; Silva, Ackson Dimas; Alvaro, Laisa Nayara; Mota, Diego Menez (Frontiers in Sustainable Food Systems, 2021)
This study aimed to evaluate the cup quality of Coffea arabica elite genotypes submitted to wet processing. C. arabica elite genotypes, which were grouped according to their genealogy: Bourbon, Paraíso Germplasm, and Resistant to Rust. Coffees were sent to wet processing to obtain fully washed coffee. After processing and drying the coffees were subjected to cup quality analysis according to the methodology of the Association of Special Coffees (SCA). To characterize and discriminate the genealogical groups the data were submitted to chemometric analysis, Principal Component Method (PCA) and Partial Least Squares Discriminant Analysis (PLS-DA). The PCA was effective in presenting an overview of the data, demonstrating the variables that most contributed to the analysis response. However, the PCA was not efficient to group genotypes according to their genealogical origin, based on chemometric data, as it is an unsupervised analysis. Even though most of the samples were classified correctly, the PLS-DA model created has not yet managed to correctly classify the genotypes of the Paraíso germplasm group. The C. arabica elite genotypes evaluated have the potential to produce special coffees, especially on the genotypes Paraíso 2, H493-1-2-10 and UFV-7158 with scores equal to or above 90 points.